Penerapan Metode Bernyanyi Dalam Meningkatkan Hasil Belajar pada Pembelajaran Pendidikan Agama Islam - Abdul Malik; Putri Dian Purnamasari; Akhmad Syahid (Education and Learning Journal, 2022)
This exploration is to further develop the results obtained from the mental, emotional, and psychomotor fields of grade 5 students in Madrasah Islamiyah subjects at SDN 056 Lamasariang, Polewali Mandar Regency. Analysts look for different sources, for example, various titles of books obtained from various libraries, bookstores, and research diaries that scientists find on the web as references in the preparation of this proposal. The exploratory strategy used in this exam is Classroom Action Research (CAR). The exam is carried out in two cycles. Each cycle consists of four phases, specifically preparation, implementation, perception, and reflection. The focus of this research is the learning outcomes of fifth graders in utilizing singing learning techniques at SDN 056 Lamasariang, Polewali Mandar Regency. The results showed that Islamic Religious Education learning by applying the singing technique learning model could further develop students' results from mental space with normal values in the pre-pattern 69.2 to 75.8 in the primary cycle, and 83.4 in the second cycle with 56 % of pre-cycle culmination, to 76% in the primary cycle and 96% in the next cycle. Meanwhile, from the emotional aspect, the assessment of students' perspectives in the main cycle, the normal perception was 72.95, increased to 83.95 in the second cycle with 65% fulfillment in the primary cycle, and the second cycle with 90%.